Deep lateral transurethral incision for vesicourethral anastomotic stenosis after radical prostatectomy. (11th August 2021) - Shinchi, Masayuki; Horiguchi, Akio; Ojima, Kenichiro; Hirano, Yusuke; Takahashi, Eiji; Kimura, Fumihiro; Ito, Keiichi
Abstract : Objectives: To investigate the outcomes of deep lateral incision for vesicourethral anastomotic stenosis after radical prostatectomy and its impact on postoperative urinary incontinence. Methods: We retrospectively investigated 43 men who underwent deep lateral incision for non‐obliterated vesicourethral anastomotic stenosis after radical prostatectomy between 2011 and 2020. The bladder neck was deeply incised through its circular fibers into the surrounding perivesical fat at 3 and 9 o'clock through electrocautery incision using needle‐type electrodes. Successful deep lateral incision was defined as the absence of additional treatment, including self‐dilatation. The postoperative urinary incontinence status was evaluated based on the number of pads used daily. Results: Deep lateral incision was successful in 35 (81.4%) patients, with a median follow‐up period of 43 months (interquartile range 15–80 months). There was no significant association of age ( P  = 0.66), body mass index ( P  = 0.49) and history of diabetes mellitus ( P  = 0.39), radiation therapy ( P  = 0.89) or previous vesicourethral anastomotic stenosis treatment ( P  = 0.71) with the incision outcomes; however, there were significantly more unsuccessful cases in those with preoperative urinary retention ( P  = 0.04) or indwelling urinary catheters for >5 days post‐incision ( P  = 0.01). A second incision was carried out in eight patients and a third incision in two patients, resulting in 42 (97.7%) successful incisions. A total of 37 (88.1%) patients had urinary incontinence and used at least one pad daily; seven (16.7%) underwent artificial urinary sphincter implantation after the last incision. Conclusions: Deep lateral incision is highly effective for treating vesicourethral anastomotic stenosis after radical prostatectomy. Appropriate treatment is required for urinary incontinence, which occurs frequently after incision.